2014
DOI: 10.1007/s00248-014-0437-y
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Distribution Along a 50 °C Temperature Gradient Reveals a Parceled Out Hot Spring Environment

Abstract: Understanding the distribution of bacteria is a major goal of microbial ecology which remains to be fully deciphered. In this study, a model 50 °C temperature gradient at a Northern Thailand hot spring was analyzed to determine how the bacterial communities were structured in the environment. Communities were examined through 16S rRNA gene amplification, denaturing gradient gel electrophoresis, and sequencing. The two major phyla, Cyanobacteria and Chloroflexi, showed characteristic distributions along the tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 53 publications
6
20
0
Order By: Relevance
“…The decline in number and diversity of microbial taxa with temperature does not appear to be linear and is steeper in the ranges corresponding to the transition between mesophily and thermophily (35-45 o C) and between thermophily and hyperthermophily (>80 o C). Such non-linear relationships have been previously reported for hot spring communities in Canada, New Zeeland, US (Nevada) and Thailand where wide temperature ranges were present within individual thermal systems [8,10,28]. ANOVA tests of potential multiple effects on the alpha diversity confirmed that, while temperature had the largest influence (P-Value from F-Ratio=3.4e-05), the individual thermal feature was significant too (P-Value from F-Ratio=3.6e-03, passing pairwise T-tests with BH-FDR).…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…The decline in number and diversity of microbial taxa with temperature does not appear to be linear and is steeper in the ranges corresponding to the transition between mesophily and thermophily (35-45 o C) and between thermophily and hyperthermophily (>80 o C). Such non-linear relationships have been previously reported for hot spring communities in Canada, New Zeeland, US (Nevada) and Thailand where wide temperature ranges were present within individual thermal systems [8,10,28]. ANOVA tests of potential multiple effects on the alpha diversity confirmed that, while temperature had the largest influence (P-Value from F-Ratio=3.4e-05), the individual thermal feature was significant too (P-Value from F-Ratio=3.6e-03, passing pairwise T-tests with BH-FDR).…”
Section: Resultssupporting
confidence: 71%
“…The dominant community members between 50-65 o C were oxygenic and anoxygenic chlorophototrophs (diverse Cyanobacteria, Choloroflexi and Chloroacidobacterium), forming characteristic green, orange and red mats depending on the site and temperature, as it has been shown in many other hot springs around the world (e.g. [28,29,[31][32][33] ). There were however some notable differences between Mirror Poll and the Icelandic features (Figure 9).…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…The influence of the molecular ecology and culturing method on the diversity, composition and dynamics of the microbial community have been investigated using cell cultures, colony counting, denaturing gradient gel electrophoresis [9,10], temperature gradient gel electrophoresis [1113], microarray [14] and length heterogeneity polymerase chain reaction [15,16]. However, a complete understanding of the microbial community remains elusive [17].…”
Section: Introductionmentioning
confidence: 99%
“…Thermal gradients in geothermal sites are thought to create habitat gradients because of the different temperature fitness of the taxa present in the communities (Miller et al, 2009, Weltzer & Miller, 2013. Although there are several studies on the structure of microbial communities along thermal gradients (Norris et al, 2002, Miller et al, 2009, Cuecas et al, 2014, none of them studied endospore formation as a survival strategy. In this study, we assess the role of endospore formation as a survival strategy along thermal gradients in a volcanic setting and compare the abundance of EFF in volcanic environments to non-extreme sites.…”
Section: Introductionmentioning
confidence: 99%